INSIDENSI DAN SEVERITAS PENYAKIT BERCAK DAUN PADA TANAMAN KACANG TANAH DI DESA LOWIAN DAN LOWIAN SATU KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN - Sammy S.N. Rori; Guntur S.J. Manengkey; Christina L. Salaki; Caroulus S. Rante (COCOS, 2014)
ABSTRACTSammy Sem Niclas Rori. Incidence and Severity of Leaf Spot Disease on Peanut Plants in the Lowian and Lowian One Village, Subdistrict Maesaan, District of South Minahasa. Under Guidence Ir Guntur S.J. Manengkey, MP as chaiman, Prof. Dr. Ir Christina L. Salaki, MS and Ir. Caroulus S. Rante, MS as member.This study aimed to determine the incidence and severity of leaf spot diseases on peanut plants. The experiment was conducted in the Lowian and Lowian One, Maesaan the District of South Minahasa Regency. The duration of the study which lasted for four months from September to December 2013. Research field using survey methods that further observation and communication with the peanut farmer. Furthermore, the distribution plots five sample plots in two different villages to be observed regarding the incidence and severity of disease caused by the cause of the peanut plant. In the laboratory microscopic observation of the shape of conidiophores of the fungus causes leaf spot disease. Things were observed in this study are: (i) symptoms of infected plants leaf spot disease-causing pathogens, (ii) the incidence and severity of disease. Observations in the field showed that the symptoms appear on peanut plants after infection by a disease that causes patches of chlorosis appear later developed into necrosis with an irregular round shape up. This phenomenon is located on the lower surface of the leaves and the leaves, leaf spot color ranging from light brown to brown or yellow halo blackish necrosis.Keywords: incidence, severity, leaf spot disease